2006
DOI: 10.1093/humrep/del124
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double-blind controlled study on the efficacy of laser zona pellucida thinning on live birth rates in cases of advanced female age

Abstract: The present study indicates that AH does not improve IVF-embryo transfer outcome in women aged > or =37 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 29 publications
0
19
0
2
Order By: Relevance
“…In addition, Lanzendorf et al (30), by using chemical AH; Edirisinghe et al (13), by using mechanical AH; and Horng et al (40) and Ali et al (41), by using LAH, failed to demonstrate any benefit of AH in improving implantation or pregnancy rates in women of advanced age. In a more recent study, Frydman et al (9) also failed to find any statistically significant difference between LAH and control groups with regard to implantation (16.1% vs. 16.7%, respectively) and live birth rates (22.4% vs. 29.6%, respectively). In contrast, Schoolcraft et al (42) observed that AH dramatically increases the implantation and pregnancy rates in patients >40 years of age.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, Lanzendorf et al (30), by using chemical AH; Edirisinghe et al (13), by using mechanical AH; and Horng et al (40) and Ali et al (41), by using LAH, failed to demonstrate any benefit of AH in improving implantation or pregnancy rates in women of advanced age. In a more recent study, Frydman et al (9) also failed to find any statistically significant difference between LAH and control groups with regard to implantation (16.1% vs. 16.7%, respectively) and live birth rates (22.4% vs. 29.6%, respectively). In contrast, Schoolcraft et al (42) observed that AH dramatically increases the implantation and pregnancy rates in patients >40 years of age.…”
Section: Discussionmentioning
confidence: 90%
“…Since then, many investigators have used the AH procedure to treat patients whose embryos undergo chemical or physical ZP changes as a possible consequence of advanced reproductive age (2,(4)(5)(6)(7)(8)(9), high FSH concentration (4,10), recurrent implantation failure (10)(11)(12)(13)(14), or cryopreservation (15)(16)(17)(18)(19). However, despite great effort, there is still considerable variation in the results reported by different investigators after the use of AH, including those who observe no advantage with the use of this method (6,9,13).…”
mentioning
confidence: 99%
“…Some of these publications reported a significant increase in the pregnancy and/or implantation rate in all patients [11]; other publications reported significant improvement in patients with a poor prognosis, namely women over 38 years of age, patients with thick zonae, and patients with repeated implantation failures [12][13][14]; while a third group of publications reported a non significant improvement in the pregnancy rate in patients with poor prognosis [11,[15][16][17][18]. On the contrary, some publications reported no improvement in pregnancy or implantation [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…[214][215][216][217][218] However, there remains conflicting evidence of an age-related benefit of assisted hatching in patients with advanced maternal age. 219,220 In an unselected population of patients, assisted hatching did not increase pregnancy and implantation rates. [221][222][223][224] A recent meta-analysis that included randomized controlled trials of assisted hatching versus no assisted hatching and reported live births, clinical pregnancies, or implantation rates, concluded that there is some evidence that assisted hatching may increase the chance of pregnancy beginning in women for whom IVF has been repeatedly unsuccessful, and possibly in older women.…”
Section: Assisted Hatchingmentioning
confidence: 82%